THE IMPROVEMENT OF TRANSPORT CONTAINERS ON THE ROUTE - Varshavets, O. V. (Science and Transport Progress, 2007)
The article describes a way to determine the optimal number of stops en route. The main point of this method is the search for extremes (in this case - the minimum) of the function, which describes the total costs of movement of the car traffic volume, i. e. the problem boils down to the optimization of the criterion function – the costs.